Di-μ-but-2-enoato-bis[diaquabis(but-2-enoato)neodymium(III)] 2,6-diaminopurine disolvate - Atria, Ana María (International Union of Crystallography, 2011)
The title Nd complex [Nd(2)(C(4)H(5)O(2))(6)(H(2)O)(4)]·2C(5)H(6)N(6) is isotypic with two previously reported Dy and Ho isologues. It is composed of [Nd(crot)(3)(H(2)O)(2)](2) dimers [crot(onate) = but-2-enoate = C(4)H(5)O(2)], built up around symmetry centres and completed by 2,6-diaminepurine molecules acting as solvates. The neodymium cations are coordinated by three chelating crotonato units and two water molecules. One of the chelating carboxylates acts also in a bridging mode, sharing one oxygen with both cations, and the final result is a pair of NdO(9) tricapped prismatic polyhedra linked to each other through a central (Nd—O)(2) loop. A most attractive aspect of the structures resides in the existence of a complex intermolecular hydrogen-bonding interaction scheme involving two sets of tightly interlinked, non-intersecting one-dimensional structures, one of them formed by the [Nd(crot)(3)(H(2)O)(2)](2) dimers running along [100] and the second by the solvate molecules evolving along [010].